Rozum rozczłonkowany. Racjonalność komunikacyjna Jürgena Habermasa .......... 101 - Smrokowska-Reichmann, Agnieszka (Na Przełomie: 25 lat seminarium filozoficznego. Uniwersytet Jagielloński 1995-2020, 2020)
REASON DISMEMBERED. COMMUNICATIVE RATIONALITY OF JÜRGEN HABERMAS Theory of communicative action by J. Habermas is a kind of decentralisation and also detranscendentalisation of reason. According to Habermas, in the postmetaphysical era philosophy should focus on the analysis and explication of rationality terms. In Habermas’s vision of rationality it is not the possession of knowledge which is the most important but rather reaching and utilizing it. Thus the huge role of three types of validity claims (regarding empirical truth, moral rightness and personal sincerity). From the perspective of Habermas’s philosophy of consensus, analysing rationality means analysing the interactions which serve as its medium and can have the character of speech or action. The process of creating objectivity consists of intersubjective exchange of judgements which is a part and parcel of understanding rationality as intersubjective judgement. Communicative action is based on pluralism but eventually it always aims to reach consensus. There are many points of view, but there is only one discourse, viewed absolutely as ideal speech situation. However, the change of paradigm from monologue to dialogue seems to have caused certain problems as regards the understanding of rationality.